Pengembangan aplikasi web tes RIASEC online pada bakat.uam.ac.id menggunakan metode Agile Scrum - Cahyono, Warna Agung (Jurnal Ilmiah Teknologi Informasi Asia, 2025)
The modern digital era has created a complex job market, increasing the need for accurate career assessment tools. The RIASEC (Realistic, Investigative, Artistic, Social, Enterprising, Conventional) test is a widely recognized framework for aligning personal characteristics with suitable work environments. However, conventional software development methods often struggle to accommodate the continuous refinement required by digital transformation and evolving user needs. This study addresses these challenges by developing an online RIASEC test web application using the Agile Scrum methodology. The research aimed to construct a flexible Scrum framework for this specific application and measure its effect on development speed. The process involved three sprints, with features defined as user stories and prioritized using MoSCoW (Must-have, Should-have, Could-have, Won't-have) rules. The results showed that the duration of sprints 1, 2, and 3 is 2 weeks, 3 weeks, and 3 weeks, respectively, with a total completion time of approximately 269 hours, 7 hours ahead of the 276-hour estimate. The study concludes that Agile Scrum is an effective approach for developing scientific web-based instruments, as it provides a structured yet flexible process that accommodates iterative feedback and successfully mitigates project risks.